Threats to soil biodiversity - global and regional trends - Brown, George (2020)
Using the information provided on the main threats in the ten ecoregions present in the six world regions (Table of threats for Sub-Saharan Africa, South West Pacific, Latin America and Caribbean, North Africa and Near East, North America and Europe; FAOand ITPS, 2015), a summary table of the main threats common to these ecoregions was produced. This exercise showed that the most widespread threat to soil biodiversity in the world was the loss of SOM and SOC, and that this could be associated with other threats such as deforestation and agricultural intensification (both linked withland use change) and with climate change (particularly in tundra). This clearly shows the importance of sustainable management and conservation practices, to maintain this resource in soils, which represents one of the bases for the soils food webs. Deforestation and agricultural intensification were also major threats worldwide, being important intropical and temperate broad leaf and mixed forests and temperate and montane grassland sand boreal forests/taiga, although the level of available information on the topic was highly variable, depending on the particular world regions where these ecoregions occur. The ecoregions with the highest number of threats were the deserts and dry shrublands, the tropical and subtropical grasslands, and the temperate broad leaf and mixed forests. Invasive species also represented an important threat, particularly in Mediterranean and temperate forests and tundra.